2010
DOI: 10.1186/1471-2407-10-659
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of platelet-derived growth factor (PDGF)-B and vascular endothelial growth factor-A expression, PDGF receptor-β phosphorylation, and microvessel density in gastric cancer

Abstract: BackgroundAngiogenesis is important in the growth and metastasis of various kinds of solid tumors, including gastric cancers. The angiogenic process is triggered by several key growth factors, including vascular endothelial growth factor (VEGF)-A and platelet-derived growth factor (PDGF)-B, that are secreted by tumors. Our aim was to define: i) the expression pattern of VEGF-A and PDGF-B in tumor cells and the activation of PDGF receptor (PDGFR)-β tyrosine kinase in stromal cells of human gastric adenocarcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 36 publications
4
71
1
2
Order By: Relevance
“…Kodama et al reported that PDGFR-β expression correlates with lymph node metastasis in gastric cancer (5). Suzuki et al showed that activation of PDGFR-β correlates with the depth of tumor invasion in gastric cancer (17), and Guo et al reported that PDGFR-β expression positively correlates with the depth of tumor invasion, lymph node metastasis and TNM stage in gastric cancer (16). By contrast, the expression levels of PDGFR-β mRNA were not associated with any clinicopathological features in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Kodama et al reported that PDGFR-β expression correlates with lymph node metastasis in gastric cancer (5). Suzuki et al showed that activation of PDGFR-β correlates with the depth of tumor invasion in gastric cancer (17), and Guo et al reported that PDGFR-β expression positively correlates with the depth of tumor invasion, lymph node metastasis and TNM stage in gastric cancer (16). By contrast, the expression levels of PDGFR-β mRNA were not associated with any clinicopathological features in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Several studies have demonstrated that the upregulation of PDGF in numerous carcinomas is able to promote lymph node metastasis and tumor cell proliferation (26,27). Importantly, it can promote the formation of tumor blood vessels and lymph vessels (28,29). Therefore, PDGF may stimulate the growth and metastasis of tumors by angiogenesis and lymphangiogenesis.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Полагают, что основ-ные механизмы могут быть связаны с секрецией иммун-ными клетками цитокинов, хемокинов, факторов роста и протеаз [6,7,10], активацией ангиогенеза [4,5,11], с участием иммунных клеток в ремодуляции экстрацеллю-лярного матрикса, способствующих инвазии опухолевых клеток и метастазированию в отдаленные органы [4,6]. Роль В-лимфоцитов в опухолевой прогрессии остает-ся малоизученной.…”
Section: Discussionunclassified